Formulation of National Defense Education Strategy in Order to Strengthen a Strong National Defense - Murfi, Yudhi; Anwar, Syaiful; Swastanto, Yoedhi; Santoso, Totok Imam; Taufik, Robby Mochamad; Maulana, Arman (Journal of Ecohumanism, 2024)
This study aims to evaluate the strategic role of the establishment of the Defense Office in the regions in coordinating and strengthening the implementation of national defense policies at the local level. The research methods used are official document analysis, case studies, and evaluation of data from various reliable sources. The results of the study indicate that although the establishment of the Defense Office in the regions faces administrative and logistical challenges, the existence of this office has strengthened coordination between the central and regional governments, and contributed significantly to the development of national resources and increasing awareness of national defense. The conclusion of this study confirms that the establishment of the Defense Office in the regions has a vital role in ensuring national security stability through the implementation of effective and efficient defense policies at the regional level.